Agreeing on Disagreement: Heterogeneity or Uncertainty? - Saskia ter Ellen; Willem F.C. Verschoor; Remco C.J. Zwinkels (Norges Bank, 2016)
Disagreement is used as a measure of both investor heterogeneity and uncertainty. We study whether disagreement captures heterogeneity or uncertainty for the foreign exchange market. We do so by relating disagreement to alternative measures of uncertainty, as well as by taking advantage of the different asset pricing implications of the two concepts. We find that whereas disagreement measures uncertainty conditionally, unconditionally this is only true during the peak of the global financial crisis.
hdl:11250/2495731
Keywords: G12; G15; 330; foreign exchange markets; disagreement; heterogeneous expectations; uncertainty